2021
DOI: 10.3390/antiox10091445
|View full text |Cite
|
Sign up to set email alerts
|

Verbascoside Protects Gingival Cells against High Glucose-Induced Oxidative Stress via PKC/HMGB1/RAGE/NFκB Pathway

Abstract: Impaired wound healing often occurs in patients with diabetes and causes great inconvenience to them. Aside from the presence of prolonged inflammation, the accumulation of oxidative stress is also implicated in the delayed wound healing. In the present study, we tested the effect of verbascoside, a caffeoyl phenylethanoid glycoside, on the improvement of cell viability and wound healing capacity of gingival epithelial cells under high glucose condition. We showed that verbascoside attenuated the high glucose-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 66 publications
1
10
0
Order By: Relevance
“…The latter species, which showed the greatest protective effect in the LDH assay ( Figure 5 ), contained the most 6-hydroxyluteolin glycosides, which were observed in G. alypum as the more potent DPPH radical scavengers (IC 50 = 6.6–12.2 µM) than its phenylethanoids (IC 50 =11.8–15.5 µM) and iridoids (IC 50 = 28.2–76.0 µM), as well as than quercetin (IC 50 = 7.8 µM) and butylated hydroxytoluene (IC 50 = 30.0 µM) [ 35 ]. Verbascoside was recently reported to protect Smulow–Glickman (S–G) gingival epithelial cells against glucose-induced oxidative stress, which may indicate its potential to improve impaired oral wound healing in diabetic patients [ 66 ]. In the same study, it was also observed to enhance mitochondrial function and improve cell survival (50 and 100 µM) in both the LDH assay and the MTT assay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter species, which showed the greatest protective effect in the LDH assay ( Figure 5 ), contained the most 6-hydroxyluteolin glycosides, which were observed in G. alypum as the more potent DPPH radical scavengers (IC 50 = 6.6–12.2 µM) than its phenylethanoids (IC 50 =11.8–15.5 µM) and iridoids (IC 50 = 28.2–76.0 µM), as well as than quercetin (IC 50 = 7.8 µM) and butylated hydroxytoluene (IC 50 = 30.0 µM) [ 35 ]. Verbascoside was recently reported to protect Smulow–Glickman (S–G) gingival epithelial cells against glucose-induced oxidative stress, which may indicate its potential to improve impaired oral wound healing in diabetic patients [ 66 ]. In the same study, it was also observed to enhance mitochondrial function and improve cell survival (50 and 100 µM) in both the LDH assay and the MTT assay.…”
Section: Resultsmentioning
confidence: 99%
“…The same compound showed potentially useful effects in other experimental diabetic complications, glucose-lowering effect in experimental T1DM and T2DM possibly due to improved glucose utilization in insulin-sensitive tissues and improved mitochondrial biogenesis/function, as well as neuroprotective and cardioprotective effect, which are all potentially linked to its antioxidant and anti-inflammatory activities [ 79 ]. Similarly, verbascoside was reported to reduce the glucose-induced production of inflammatory cytokines, IL-6 and IL-1β in Smulow-Glickman gingival epithelial cells exposed to high glucose concentrations [ 66 ], as well as to reduce cellular inflammation and improve mitochondrial activity and survival of pancreatic β-cells under endoplasmic reticulum-stress [ 82 ]. Asperuloside and asperulosidic acid, which were observed in G. punctata , G. cordifolia and G. meridionalis , significantly decreased the production of NO, PGE 2 , TNF-α, and IL-6, and inhibited the expression of inducible NO synthase (iNOS), COX-2, TNF-α, and IL-6 mRNA in LPS-induced RAW 264.7 cells [ 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sasa borealis water-extract blocks chronic high glucose-induced endothelial apoptosis by the blunting activation of βII and NADPH oxidase promoted [139]. Furthermore, verbascoside downregulated expression of the inflammatory cytokines IL-6 and IL-1β by inhibiting PKC/HMGB1/RAGE/NFκB signaling and ultimately may be beneficial to oral wound healing in diabetic patients [140]. From these findings, we speculate that these PKC-targeted natural biologics for diabetes and its other complications may be potential strategies for DFU therapy because of their same or similar pathogenesis.…”
Section: Pkc Pathwaysmentioning
confidence: 99%
“…Verbascoside (VER), a phenylethanoid glycoside, is one of the most widespread and potent among the reported polyphenols . VER was reported to attenuate cytotoxicity induced by elevated glucose levels and to reduce oxidative stress by downregulation of PKC/HMGB1/RAGE/NFκβ signaling . Recently, VER isolated from Odontonema strictum in an aqueous medium showed effective free radical scavenging activities .…”
Section: Introductionmentioning
confidence: 99%